Mutational analysis of Arabidopsis thaliana plant uncoupling mitochondrial protein - Favaro, Regiane Degan [UNESP]; Borecky, Jiri; Colombi, Debora [UNESP]; Vercesi, Anibal E.; Maia, Ivan de Godoy [UNESP] (Elsevier B.V., 2007)
In this study, point mutations were introduced in plant uncoupling mitochondrial protein AtUCP1, a typical member of the plant uncoupling protein (UCP) gene subfamily, in amino acid residues Lys147, Arg155 and Tyr269, located inside the so-called UCP-signatures, and in two more residues, Cys28 and His83, specific for plant UCPs. The effects of amino acid replacements on AtUCP1 biochemical properties were examined using reconstituted proteoliposomes. Residue Arg155 appears to be crucial for AtUCP1 affinity to linoleic acid (LA) whereas His83 plays an important role in AtUCP1 transport activity. Residues Cys28, Lys147, and also Tyr269 are probably essential for correct protein function, as their substitutions affected either the AtUCP1 affinity to LA and its transport activity, or sensitivity to inhibitors (purine nucleotides). Interestingly, Cys28 substitution reduced ATP inhibitory effect on AtUCP1, while Tyr269Phe mutant exhibited 2.8-fold increase in sensitivity to ATP, in accordance with the reverse mutation Phe267Tyr of mammalian UCP1. (C) 2007 Elsevier B.V. All fights reserved.
Keywords: uncoupling protein; Arabidopsis thaliana; site-direct mutagenesis; proteoliposome; structure-function relationship